Managers' financial practices and financial sustainability of Nigerian manufacturing companies: Which ratios matter most? - Japhet Osazefua Imhanzenobe (Cogent Economics & Finance, 2020)
The study aims to identify which aspects of financial practices of managers need to be given priority in achieving a turnaround in the financial sustainability of these manufacturing companies across long-term returns, sustainable growth and financial distress. Currently, the Nigerian manufacturing sector experiences a decline in financial sustainability, thus forcing financially unsustainable companies out of business. Financial practices that improve the long-term financial position and performance need to be implemented. These financial practices can be measured across short-term profitability, efficiency, liquidity and solvency. Some studies have considered sustainability from a financial perspective using one or two measures but very few focus on the Nigerian manufacturing sector. This study fills these gaps by investigating the impact of financial practices on financial sustainability across these measures. Panel dataset for 17 companies from 2008 to 2016 was collected and analysed using the correlation matrix and random effect model. All regressors were significant in explaining financial distress. However, only short-term profitability and efficiency ratios were consistently significant across all three models, thus indicating the superiority of financial practices that affect short-term profits and efficiency. The study recommends that companies should implement financial policies that address periodic costs and productivity while maximizing marketing efforts simultaneously.
Keywords: M41; 330; financial sustainability; financial ratio; earnings management; sustainable growth; financial distress